Utility of a novel perceptual-motor control test for identification of sport-related concussion beyond current clinical assessments - Eagle, S. R.; Kontos, A. P.; Sinnott, A.; Beckner, M.; Nindl, B. C.; Flanagan, S. D.; Lovalekar, M.; Connaboy, C. (Journal of Sports Sciences, 2020)
Clinically feasible metrics, that can inform the concussion recovery decision making process by evaluating a unique domain beyond current testing domains (e.g., balance, neurocognition, symptoms, vestibular/ocular function) are still in need. The purpose of this study was to compare perceptual-motor control in adolescent athletes =21 days of sport-related concussion and healthy controls and evaluate the association of perceptual-motor control to the outcomes of commonly-used sport-related concussion clinical assessments. Athletes (age: 12-18 years) with sport-related concussion (n = 48) and healthy controls (n = 24) completed the Perception-Action Coupling Task (PACT), whose outcomes are mean reaction, movement, initiation, response time, and accuracy. ImPACT outcomes are verbal/visual memory scores, motor processing speed, and reaction time. Vestibular-Ocular Motor Screen (VOMS) outcomes are symptoms from: smooth pursuit, horizontal/vertical saccades, near-point of convergence, horizontal/vestibular ocular-reflex, and visual motion sensitivity. CONCUSSED demonstrated ~5% deficit in overall perceptual-motor accuracy during PACT compared to CONTROLS (p = 0.03). PACT accuracy negatively correlated with smooth pursuits(r = -0.29), and horizontal (r = -0.35)/vertical (r = -0.30) saccades. The C5.0 decision tree determined PACT accuracy was the most relevant predictor of sport-related concussion when no visual motion sensitivity symptoms were reported and Visual Memory was >66. Perceptual-motor control tests may complement current sport-related concussion assessments when neurocognition and vestibular/ocular motor system are not grossly impaired.